2012
DOI: 10.1890/11-1247.1
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting mycorrhizal mutualisms: a potential mechanism by which exotic tamarisk outcompetes native cottonwoods

Abstract: The disruption of mutualisms between plants and mycorrhizal fungi is a potentially powerful mechanism by which invasives can negatively impact native species, yet our understanding of this mechanism's role in exotic species invasion is still in its infancy. Here, we provide several lines of evidence indicating that invasive tamarisk (Tamarix sp.) negatively affects native cottonwoods (Populus fremontii) by disrupting their associations with arbuscular mycorrhizal (AM) and ectomycorrhizal (EM) fungi. At a field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 111 publications
5
92
1
Order By: Relevance
“…Arbuscule occurence showed the same trend in the case of F. vaginata, whereas for S. borysthenica vesicle occurence was markedly lower in C. dactylon stands than in uninvaded habitats. Others also reported decreased mycorrhizal colonisation of plants near invaders (Stinson et al 2006, Zhang et al 2007, Meinhardt et al 2012. A possible mechanism responsible for our findings is explained by the degraded mutualist hypothesis, for which Bever et al (2010) suggested a conceptual model, namely that the dominant species inhibits the mutualists of the resident community.…”
Section: Stipa Borysthenica) In Uninvaded Semi-natural Habitats and Isupporting
confidence: 59%
See 1 more Smart Citation
“…Arbuscule occurence showed the same trend in the case of F. vaginata, whereas for S. borysthenica vesicle occurence was markedly lower in C. dactylon stands than in uninvaded habitats. Others also reported decreased mycorrhizal colonisation of plants near invaders (Stinson et al 2006, Zhang et al 2007, Meinhardt et al 2012. A possible mechanism responsible for our findings is explained by the degraded mutualist hypothesis, for which Bever et al (2010) suggested a conceptual model, namely that the dominant species inhibits the mutualists of the resident community.…”
Section: Stipa Borysthenica) In Uninvaded Semi-natural Habitats and Isupporting
confidence: 59%
“…For example, such a mechanism has been reported for the European Alliaria petiolata in North American forests (Stinson et al 2006, Hale et al 2011, but see Barto et al 2010). Alternatively, the soil microbial community may be changed indirectly via the mass effect of the invasive plant being non-mycorrhizal or having different AMF symbionts, hence local AMFs gradually attenuate (Niu et al 2007, van der Putten et al 2007, Vogelsang and Bever 2009, Meinhardt and Gehring 2012, Sanon et al 2012. Different AMF species may have different colonisation phenologies (see e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, these changes in soil communities usually promote the growth of invasive plants, yet inhibit native plant performance, mainly driven by the lack of soil pathogens to invasive plants in the new habitats [14,15], the preferential enrichment of microbial pathogens to native plants [16,17], or the inhibition of microbial mutualism with native plants [18][19][20].…”
mentioning
confidence: 99%
“…A. petiolata reduced the diversity and abundance of AMF due to the production of allelochemicals (Roberts & Anderson, 2001). Another nonmycorrhizal exotic invasive plant species Tamarix retarded the growth of native plant Populus fremontii S. Watson by interrupting its mutualistic association with AM fungi and EMF (Meinhardt & Gehring, 2012). An invasive plant, Impatiens glandulifera Royle in a mixed deciduous forest had a negative effect on the mutualistic association between AM fungi and the native plant Acer pseudoplatanus L. (Ruckli et al, 2014).…”
Section: Role Of Mycorrhizal Symbiosis In Plant Invasionmentioning
confidence: 99%